As criações neológicas em Monteiro Lobato: para a construção de um glossário - Cardoso, Nilza Aparecida Alves (2006)
This research had for objective to study the lexis of Urupês , by Monteiro Lobato and make a glossary of the neologisms found in that work. It is linked to the project named 'Dictionaries of the Literary Neologisms of the Portuguese Language of Brazil', Master's degree program in Linguistics of the Universidade Federal de Uberlândia. Our hypothesis is that Lobato looks for the construction of unusual words which represent the poetic effect he intends to present. He works on the lexicon of the Portuguese Language in the attempt of contextualizing the characters that are far from the urban areas. Another hypothesis would be that his lexical creations can affectively rescue the time and the author's experiences. Our work firstly consisted of the selection of nouns, adjectives and verbs that are presented in Lobato s work, which is our research object. To verify the neological character of this lexis, dictionaries of certain periods of time and the foundations of Boulanger s theory (1979) were used as the exclusion corpus . We then, made the analysis of the words contextual sense, adding some other information we considered as relevant. After the research we verified that one or our main work hypotheses was confirmed, once we found a significant number of neologisms in the author s work. Studying the selected words, we still noticed the expressiveness of the word elements which were used by the author. Finally we can conclude that Monteiro Lobato built his neologisms with the knowledge he had of the structure of his mother tongue, what favored, in a certain way, the construction of senses for the words. Besides, his lexical creations acquire an unpublished sense in the literary context where one can find the register.